Transfer Pricing dan Capital Intensity Pada Agresivitas Pajak: Diversifikasi Gender Sebagai Pemoderasi - Puti Syifa Imani; Ferry Irawan (Jurnal Ekonomi, 2025)
The government seeks to increase revenue through tax revenue, while companies as taxpayers want to maximize profits by paying as little tax as possible. Therefore, companies design various legal and illegal tax planning strategies known as tax aggressiveness. This study aims to analyze the effect of transfer pricing and capital intensity on tax aggressiveness with gender diversification as a moderator. This study uses a quantitative approach with moderated regression analysis (MRA) on energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. Purposive sampling technique was used for sample selection, resulting in 160 samples. The results of the study indicate that transfer pricing has no effect on tax aggressiveness, while capital intensity has a positive effect on tax aggressiveness. Meanwhile, gender diversification is unable to moderate the effect of transfer pricing or capital intensity on tax aggressiveness.